2022
DOI: 10.1155/2022/8158699
|View full text |Cite
|
Sign up to set email alerts
|

Flos Carthami Exerts Hepatoprotective Action in a Rat Model of Alcoholic Liver Injury via Modulating the Metabolomics Profile

Abstract: This study was intended to identify the shifts in the metabolomics profile of the hepatic tissue damaged by alcohol consumption and verify the potential restorative action of flos carthami (the flowers of Carthamus tinctorius, FC) in the protection of alcohol-induced injury by attenuating the level of identified metabolites. Rats were treated with FC and subsequently subjected to alcohol administration. The serum samples were subjected to liquid chromatography-mass spectrometry (LC-MS)-based metabolomics follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…Alcoholic liver injury is usually associated with metabolic disturbances caused by changes in the metabolite profile. 40 Serum liver indices, as well as HE-stained sections, confirmed that CAROL can effectively reduce oxidative stress and hepatocyte injury with hepatoprotective effects. On this basis, UPLC-QTOF-MS non-targeted metabolomics technique was used to study the changes of metabolites in liver-injured rats after drug administration.…”
mentioning
confidence: 72%
“…Alcoholic liver injury is usually associated with metabolic disturbances caused by changes in the metabolite profile. 40 Serum liver indices, as well as HE-stained sections, confirmed that CAROL can effectively reduce oxidative stress and hepatocyte injury with hepatoprotective effects. On this basis, UPLC-QTOF-MS non-targeted metabolomics technique was used to study the changes of metabolites in liver-injured rats after drug administration.…”
mentioning
confidence: 72%
“…In this study, we employed metabolomic approaches to identify potential early biomarkers for predicting liver injury and metabolic abnormalities by analyzing differential metabolites following liver injury [ 27 ]. Currently, mice with ALD are commonly utilized to investigate the metabolic profiles in serum, urine, and liver tissue using techniques such as magnetic resonance (NMR) spectroscopy, gas chromatography-mass spectrometry (GC-MS), and liquid chromatography/tandem mass spectrometry (LC-MS) [ 28 ]. Previous studies on ALD analysis using metabolomics have primarily focused on phospholipid metabolism [ 29 ], amino acid metabolism [ 30 , 31 ], and energy metabolism [ 32 ].…”
Section: Discussionmentioning
confidence: 99%